5y-6-3y+5=0

Simple and best practice solution for 5y-6-3y+5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-6-3y+5=0 equation:


Simplifying
5y + -6 + -3y + 5 = 0

Reorder the terms:
-6 + 5 + 5y + -3y = 0

Combine like terms: -6 + 5 = -1
-1 + 5y + -3y = 0

Combine like terms: 5y + -3y = 2y
-1 + 2y = 0

Solving
-1 + 2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 2y = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 2y = 0 + 1
2y = 0 + 1

Combine like terms: 0 + 1 = 1
2y = 1

Divide each side by '2'.
y = 0.5

Simplifying
y = 0.5

See similar equations:

| sin9pie/3 | | 81=9x+9 | | 4x-6x+x-4+5x= | | 2/9-31=16=7/9 | | x^2-15x-52=0 | | 9=a/3-4 | | -3b+10(b-4)=-110 | | 8(x+4)-6x=x-2 | | 1-7x-1=-21 | | 5m+10=5m-10 | | -23=-4x-x-8 | | 6.1x-3+x-1.3= | | 29=10n+9 | | 5-8(s+1)=-9s+4 | | 6y-1= | | 0.3x-17=1.1x-25 | | 4/5x-1/5=9 | | 2(x+5)=36 | | 3x(x-2)+(x-2)= | | 3a+5+4a-6=2 | | x^2-10+11=0 | | -5-1.2= | | 2*log*x=log*2+log(3*x-4) | | 10+x-7x=-38 | | 8x+6(1+5x)=2 | | 6.1+1= | | 7+7k=147 | | 2/3m-1/3=5/12 | | 8-3y=2(3+y)-5 | | -2(n-4)=10-2N | | -2y-5+2y^2=0 | | 8x+6(1+5x)= |

Equations solver categories